Movimento sociais e formação de professoras e professores de ciências em artigos nacionais e internacionais - Souza, Ivania Aparecida de (2021)
The present work aimed to identify if there is a contribution of scientific research that articulates the formation of teachers and social movements. We emphasize that this theme is related to the training of professionals who practice critical reflection, praxis and dialogue (FREIRE & SHOR, 1986) when teaching their subjects. The research had data collection on a qualitative basis, having as reference the bibliographical research (LIMA and MIOTO, 2007) where four articles were found, two Brazilians and two Colombians, and the analysis was performed according to the theory of Discursive Textual Analysis (ATD) (MORAES and GALIAZZI, 2006). When developing the processes indicated in the ATD, we highlighted more than one category for each of the articles and the analyzes were carried out according to categories defined a priori. Data collection was performed using the descriptors of teacher education and social/popular/popular social movements, along with the Web of Science and Scielo databases, with a chronological parameter established for the period between 2011 and 2020. Through these searches, they were selected four articles that were within the established parameters and through the analysis of the documents we were able to identify theoretical approaches by some, and approaches to the critical reflections that the authors inserted throughout the text, some of which will be highlighted. We conclude that the field of research involving the training of female teachers and social movements has a scarcity of publications, especially when we think about the training of female teachers specifically for the teaching of science, which indicates that it is an area with perspectives for future research.